Penyebaran dan Karakteristik Zirkon Dasar Laut sebagai Endapan Sekunder di Perairan Singkawang dan sekitarnya, Kalimantan Barat - Aryanto, Noor Cahyo; Kurnio, H. (Indonesian Journal on Geoscience, 2010)
DOI:Â 10.17014/ijog.v5i2.98The abundance of sea floor zircon mineral in the studied area was found at the southwest of Kabung Island (SKWL-56) which was accumulated in silty sand sediments at 23 m water depth. Based on the grain mineragraphy analysis, this mineral has various characteristics: rose, white, and brownish yellow colours, elongated prismatic crystals, and translucent to transparent appearances. The distribution profile lines have shown that the distribution of seafloor zircon tends to decrease from Kabung and its surrounding areas to Lemukutan, and from Kabung to the Land of Kalimantan. Considering the abundances, distribution, crystal shape, and mineral association, the zircon mineral in the studied area is a placer deposit that was produced by transport processes characterized by the changing form of crystal. Some samples observed, showed corrosion marks due to a transportation activity, while the transparent level change of these minerals was suggested to be due to much penetration into cavities in the mineral, which lead to the presence of gangue material during the deposition process.